Systém odměňování zaměstnanců a návrh na zlepšení ve vybrané společnosti - Šmídová, Jaroslava (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Bakalářská práce se zaměřuje na systém odměňování zaměstnanců ve vybrané společnosti. První část je zaměřena na teoretické poznatky týkající se systémem odměňování získaných z odborné literatury. Druhá část je věnována analýze současného stavu ve vybrané společnosti a spokojenost zaměstnanců s ním. Ve třetí části jsou představeny návrhy na zlepšení aktuálního systému odměňování ve společnosti.

The bachelor thesis focuses on the employee remuneration system in a selected company. The first part focuses on the theoretical knowledge related to the remuneration system obtained from the literature. The second part is devoted to the analysis of the current situation in the selected company and employee satisfaction with it. The third part presents suggestions for improving the current remuneration system in the company.
Employee remuneration system and proposal of changes to its improvement in the selected company
Keywords: systém odměňování; zaměstnanecké benefity; zaměstnanec; zaměstnavatel; motivace; mzda; reward system; employee benefits; employee; employer; motivation; wage